REAL-TIME SCHEDULING BASED ON SELF-DISTRIBUTED PRODUCTION SYSTEMS AND CONFIGURABLE VIRTUAL WORKSTATIONS: JOB SHOP PRODUCTION CASE STUDIES - Yusuf Ahmadi, Baharuddin
Production scheduling is an essential aspect of the production system. In the production system, scheduling plays a role in resource allocation on the production floor. Scheduling also plays a significant role in fulfilling orders on time. However, in practice, the scheduling results often do not align with the actual conditions on the production floor due to delays in information transmission from the production floor. In job shop production systems, these changes in conditions frequently occur because job shop production systems are required to have high flexibility. By utilizing the CVWs (Configurable Virtual Workstation) framework, a real-time scheduling system for job shop production systems can be developed to ensure that the scheduling decisions are relevant to the current production floor conditions. The results obtained in this research demonstrate the successful development of a real-time scheduling system based on Self-Contained Distributed Production System and CVWs, as evidenced by comparing the scheduling program's test results for all cases used with the calculations derived from the analytical method. Additionally, the time required for scheduling is short and approaches real-time, enabling the developed real-time scheduling system in this research to perform scheduling in real-time.